Penerapan COBIT 5.0 Domain Deliver, Service And Support (DSS) Untuk Audit Sistem Informasi NOSS-A (Studi Kasus : Telkom Witel Manado) - Joe Yuan Mambu; Mirielle Patricia Huwae; Erienika M Lompoliu (Electro Luceat, 2021)
Information systems have become one of the fundamental requirements for organizations or companies. With an information system, business processes can run more effectively. Next Generation Operation Support System Assurance (NOSS-A) is an information system used by PT. Telekomunikasi Indonesia Tbk, to monitor and record internet disruption complaints of Indihome service. The NOSS-A Information System manages a lot of data related to customer and staff data. For this reason, in this study, the research was carried out to audit the NOSS-A information system to see whether there is a need for an improvement in the information system, based on audit results that can show the impact of the effectiveness and capability level achieved. The audit standard used in this study is COBIT 5.0 with the domain Deliver, Service and Support. The results obtained from this study are the NOSS-A Information System is at level 4 which means the activities on the DSS domain has been done and monitored regularly. The NOSS-A Information System needs to have a regular evaluation with target improvement to increase its level in the future.